Barings' crisis and SIMEX : a case study. - Chow, Winnifred Cheok Kuan. (2013)
The bankruptcy of Barings plc, brought about by massive derivative losses, was one of the major financial events in the year of 1995. It turnedthe world's attention to derivative trading and the risks and pitfalls asscociated with it. Since this crisis orchestrated in the Singapore International Monetary Exchange (SIMEX), our report aims to examine the effects and implications that the event had on the exchange. In the report, we first provide our reades with a background to derivative trading. This is followed by an insight to the Barings' crisis. Statistical tests are then conducted to examine whether any abnormal returns could be earned on SIMEX and also, if investors' confidence on the exchange was shaken during the period of study. Finally, the existing regulatory framework of SIMEX is evaluated.